Synergistic mosquito-repellent activity of Curcuma longa, Pogostemon heyneanus and Zanthoxylum limonella essential oils. Issue 4 (July 2015) - Das, N.G.; Dhiman, Sunil; Talukdar, P.K.; Rabha, Bipul; Goswami, Diganta; Veer, Vijay
Summary Mosquito repellents play an important role in preventing man–mosquito contact. In the present study, we evaluated the synergistic mosquito-repellent activity of Curcuma longa, Pogostemon heyneanus and Zanthoxylum limonella essential oils. The mosquito repellent efficacies of three essential oils were evaluated separately and in combination under laboratory and field conditions. N, N-Diethylphenylacetamide (DEPA) and dimethylphthalate (DMP) were used for comparison of the protection time of the mixture of essential oils. At an optimum concentration of 20%, the essential oils of C. longa, Z. limonella and P. heyneanus provided complete protection times (CPTs) of 96.2, 91.4 and 123.4 min, respectively, against Aedes albopictus mosquitoes in the laboratory. The 1:1:2 mixture of the essential oils provided 329.4 and 391.0 min of CPT in the laboratory and field trials, respectively. The percent increases in CPTs for the essential oil mixture were 30 for DMP and 55 for N, N-diethylphenylacetamide (DEPA). The synergistic repellent activity of the essential oils used in the present study might be useful for developing safer alternatives to synthetic repellents for personal protection against mosquitoes.